Infrared radiation and thermal properties of Al-doped SrZrO3 perovskites for potential infrared stealth coating materials in the high-temperature environment. Issue 16 (15th August 2021) - Li, Enbo; Bai, Yu; Dong, Hongying; Jia, Ruiling; Zhao, Xueping; Wang, Ruijun; Bao, Manyu; Ma, Wen
Abstract: The Al-doped SrZrO3 perovskite powder with low infrared emissivity at high temperatures was prepared. The infrared radiation performance and thermophysical properties of the perovskites at high temperatures were discussed. As a result, the infrared emissivity of the Al-doped SrZrO3 perovskite powder is associated with Al 3+ -doping content, phase composition and particle morphology. The flaky particles SrZr0.85 Al0.15 O2.925 formed by heat treatment at 1000 °C for 6 h have the lowest infrared emissivity of 0.245 in 3–5 μm wavebands at 590 °C. The perovskite powder's infrared emissivity is positively correlated with its electrical resistivity and has no apparent change after heating over 800 °C for long-term. The SrZr0.85 Al0.15 O2.925 perovskite ceramic formed by pressureless sintering still maintains ideal heat insulation performance with the thermal conductivity from 1.17 to 2.21 W m −1  K −1 below 1400 °C. The Al-doped SrZrO3 perovskite tablet exhibits significant weak radiation intensity due to its characteristics of both low infrared emissivity and thermal conductivity at high temperatures.